2015
DOI: 10.1038/ncomms8672
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern from birth to adulthood in African pygmies of known age

Abstract: The African pygmy phenotype stems from genetic foundations and is considered to be the product of a disturbance in the growth hormone–insulin-like growth factor (GH–IGF) axis. However, when and how the pygmy phenotype is acquired during growth remains unknown. Here we describe growth patterns in Baka pygmies based on two longitudinal studies of individuals of known age, from the time of birth to the age of 25 years. Body size at birth among the Baka is within standard limits, but their growth rate slows signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
59
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 43 publications
7
59
1
3
Order By: Relevance
“…Adult height (average for males = 153.5 cm, average for females = 146.7 cm) is attained at 20 and 18 years respectively. LHV in the Baka (median age at menarche age at first pregnancy, interbirth interval) do not differ from those in standard populations16.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Adult height (average for males = 153.5 cm, average for females = 146.7 cm) is attained at 20 and 18 years respectively. LHV in the Baka (median age at menarche age at first pregnancy, interbirth interval) do not differ from those in standard populations16.…”
mentioning
confidence: 68%
“…Recently, based on the most extensive study on pygmies to date, we suggested that the pygmy phenotype in the Baka from south-eastern Cameroon results from changes in growth during earliest infancy, and therefore that the pygmy phenotype results from a low growth rate during the first 2 years of life, which produces a lasting delay in overall growth compared with standard ref. 16. Adult height (average for males = 153.5 cm, average for females = 146.7 cm) is attained at 20 and 18 years respectively.…”
mentioning
confidence: 98%
“…The competing explanations or adaptive foundations for size reduction ('dwarfing') in modern pygmies include thermoregulation, nutrition/diet, locomotion in closed habitats and life-history trade-offs related to early sexual maturation in high mortality environments [31,75]. Each of these explanations has shortcomings or limitations [76], but it seems clear now that the pygmy phenotype has evolved convergently in Africa, Asia and Melanesia [75,77]. Regardless of the adaptive (or not) basis of body size reduction in human pygmies, these dwarfing explanations may not apply to early hominins if small body size is the primitive condition [75].…”
Section: Size and Limb Proportionsmentioning
confidence: 99%
“…Draper and Howell, 2005; Foster et al, 2005; Walker et al, 2006; Rozzi et al, 2015; Urlacher et al, 2016) detailed descriptions from large samples with accurate ages are rare and few growth references derived specifically for indigenous populations are available. Given the high degree of individual variability in growth, conclusions about growth based on small samples are often problematic or inconclusive.…”
Section: Introductionmentioning
confidence: 99%